Implementing hospital guidelines improves warfarin use in non-valvular atrial fibrillation: a before-after study - Piobbici Marina; Boscolo Daniela; Scaglione Luca; Valpreda Susanna; Bo Simona; Bo Mario; Ciccone Giovannino (BMC, 2007)
Abstract Background The use of oral anticoagulant therapy (OAT) to prevent non-valvular atrial fibrillation (NVAF) related-strokes is often sub-optimal. We aimed to evaluate whether implementing guidelines on antithrombotic therapy (AT) by a multifaceted strategy may improve appropriateness of its prescription in NVAF-patients discharged from a large tertiary-care hospital. Methods A survey was conducted on all consecutive NVAF patients discharged before (1st January-30th June 2000, n = 313) and after (1st January-30th June 2004, n = 388) guideline development and implementation. Results When strongly recommended, OAT use increased from 56.6% (60/106 in 2000) to 81.9% (86/105 in 2004), with an absolute difference of +25.3% (95%CI: 15% 35%). In patients for whom the choice OAT/acetylsalicylic acid should be individualised, those discharged without any AT were 33.7% (34/101) in 2000 and 16.9% (21/124) in 2004 (-16.7%;95%CI: -26.2% -7.2%). In a logistic regression model, OAT prescription in 2004 was increased by 2.11 times (95%CI: 1.47 3.04), after accounting for stroke risk, presence of contraindications (OR = 0.18; 0.13 0.27), older age (OR = 0.30; 0.21 0.45), prophylaxis at admission (OR = 3.03; 2.08 4.43). OAT was positively associated with the stroke risk in the 2004 sample only. Conclusion The guideline implementation has substantially improved the appropriateness of OAT at discharge, through a better evaluation at patient's individual level of the benefit-to-risk ratio.